ANALISIS ETIKA PELAYANAN PUBLIK: Studi Pada Kantor Badan Perencanaan Pembangunan Daerah Provinsi Sulawesi Utara - Mutiara Timbuleng; Ryan Aji Johannes; Itje Pangkey; Fitri Herawati Mamonto (Jurnal Ilmiah Administrasi Pemerintahan Daerah, 2023)
Ethical considerations in the implementation of public services have serious implications for developing public issues, where negligence in complying with moral principles can result in inequality in public policy. This negative impact can involve individuals or groups who become victims of immoral policies. Public services, as an instrument for improving collective welfare, are threatened with being marginalized due to inadequate services, less than optimal implementation of tasks, and the tendency to prioritize personal and certain group interests. This research aims to analyze Public Service Ethics at the North Sulawesi Province Regional Development Planning Agency Office. The research method used is qualitative descriptive research, with data collection techniques through observation, interviews and documentation. The data obtained was analyzed descriptively qualitatively. The research results show that implementation of the concepts of equal rights, justice, loyalty and responsibility is not yet optimal. In terms of equal rights, it appears that awareness of the importance of providing equal services to all citizens is still low among employees. In the aspect of justice in public services, it is also still hampered by limited facilities, lack of emphasis on honesty, and personal interference which creates inequality. In the dimension of employee loyalty to their duties and responsibilities, it has also not reached the optimal level. Factors such as the dynamics of the work environment, lack of time discipline, resistance to criticism, and lack of awareness of responsibility affect employee performance. Therefore, to improve the quality of public services, it is necessary to carry out improvement efforts that focus on increasing employee awareness, discipline and loyalty to their duties and responsibilities. Implementation of strong public service ethics is the key to creating a service environment that is equal, fair and responsive to community needs.